Perancangan Media Pembelajaran Dasar Desain Grafis Berbasis Android Siswa SMK Jurusan Teknik Komputer dan Jaringan (TKJ) - Jhon Veri; Popi Radyuli; Angga Kurnia Putera (Universitas Putra Indonesia YPTK Padang, 2020)
This study aims to create an Android-based learning media that meets the valid, practical and effective requirements for Basic Graphic Design subjects. This research is a Research and Development research conducted at SMK. The test subjects in this study were students of class X TKJ SMK Negeri 5 Padang. The results of the assessment of the three validators as a whole are 85.31% so that the level of validity can be interpreted as valid. The overall assessment of practicality is 91.66%, so that the level of practicality can be interpreted to be very practical to use, and the effectiveness rating is 85.92%, so that the level of effectiveness can be interpreted properly.